A descriptive study to determine the prevalence of TPMT polymorphism in Healthy male subjects in Central South Africa - Ferreira, Maria Magdalena (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)--Stellenbosch University, 2014.